Posterior Reversible Encephalopathy Syndrome. A case report. - ANAYO , Nyinèvi Komla; GUINHOUYA, Kokou Mensah; APETSE , Kossivi; AGBA , Léhleng; ASSOGBA , Komi; BELO , Mofou; BALOGOU, Koffi A. (Jour Med Resh and Health Sci, 2022)
We report a case of posterior reversible encephalopathy syndrome (PRES) in a 52-year-old patient with a history of chronic unmonitored hypertension who was brought to the emergency department for sudden onset of seizures, headache and confusion while driving, leading to a violent traffic accident. Magnetic resonance imaging (MRI) Flair sequence showed hypersignals of the posterior cerebral fossa corresponding to vasogenic edema. The radio-clinical evolution was favorable under symptomatic treatments with a disappearance of the hypersignals three months after the beginning of the symptoms. It seems important to think of a RPRS in front of a picture of confusion, headaches and seizures in a context of malignant hypertension badly followed.